2019
DOI: 10.3390/en12040700
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Power Generation by Offshore Wind Farms Using Multiple Data Sources

Abstract: In this study we evaluated the wind resources of wind farms in the Changhua offshore area of Taiwan. The offshore wind farm in Zone of Potential (ZoP) 26 was optimized through an economic evaluation. The annual energy production (AEP) of the offshore wind farm in ZoP 26 was predicted for 10 and 25 years with probabilities of 50%, 75%, and 90% by using measured mast data, measure-correlate-predict (MCP) data derived from Modern-Era Retrospective Analysis for Research and Applications (MERRA), and Central Weathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…There are some sources for collecting offshore wind speed data, such as historical data, wave-buoys, remote sensing from satellites, national weather ships, coastal meteorological stations, and statistical distribution (Foley et al, 2012). Previous studies have shown that the Weibull distribution is a good representation of hourly wind speed variations at a location (Shu et al, 2015;Yue et al, 2019). The Weibull distribution is fitted to wind speed data to calculate the shape and scale parameters for a specific location.…”
Section: Production Objectivementioning
confidence: 99%
“…There are some sources for collecting offshore wind speed data, such as historical data, wave-buoys, remote sensing from satellites, national weather ships, coastal meteorological stations, and statistical distribution (Foley et al, 2012). Previous studies have shown that the Weibull distribution is a good representation of hourly wind speed variations at a location (Shu et al, 2015;Yue et al, 2019). The Weibull distribution is fitted to wind speed data to calculate the shape and scale parameters for a specific location.…”
Section: Production Objectivementioning
confidence: 99%
“…The cumulative installed capacity prediction of offshore wind farms is a complex nonlinear solution problem. So far, many scholars have proposed various prediction models for wind energy installation predictions in various countries 32‐44 . Vahidzadeh and Markfort 32 predicted the turbine power output curve by using a high‐resolution wind measurement power curve, including turbulence, yaw error, air density, wind direction, and shear; Huan et al 33 proposed a combined prediction model based on Set Empirical Mode Decomposition (EEMD) and Least‐Squares Support Vector Machine (LSSVM) to improve the accuracy and effectiveness of dissolved oxygen (DO) prediction; Kim and Hur 34 proposed a random prediction of wind power resources for the Jeju Island wind farm in South Korea using the enhanced set model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Particularly, photovoltaic (PV) generators acquire special relevance in SGs and SMGs, due to the fact that they are commonly the main source of renewable energy in this type of system. Wind generators can provide enormous amounts of energy, but still present problems of predictability [5].…”
Section: Introductionmentioning
confidence: 99%